Design and Development of a Smart Cane Using Ultrasonic Sensors and GPS for Visually Impaired people - Amier A. Frag; Omran A. H. Mohamed; Massoud A. Omar Imaezeg; Yaser S. A. Shaheen (African Journal of Advanced Pure and Applied Sciences, 2025)
This paper presents the design and development of a smart cane for the visually impaired, utilizing ultrasonic sensors and a microcontroller to enhance mobility and obstacle detection. The system detects obstacles within a range of up to 3 meters, covering both front and lateral directions, and provides real-time feedback through vibration and sound alerts. The cane also integrates a GPS module for real-time location tracking and safety monitoring. The prototype was tested with 8 individuals (4 visually impaired, 4 sighted with blindfolds) across five different environments (indoor, outdoor, stairs, uneven terrain, and crowded areas). Results showed an obstacle detection accuracy of 95.4%, a false alarm rate of 2.6%, and a 30% improvement in navigation speed compared to the traditional white cane. The findings demonstrate that the proposed smart cane is an effective, low-cost, and reliable assistive device for improving independent mobility among visually impaired individuals.